Hubungan Antara Intensi Kepedulian Terhadap Kesehatan Maternal Dan Kompetensi Interpersonal Bidan Di Desa - Frandsca Maristha Josef (Jurnal Psikologi, 2005)
This study assesses the effect of interpersonal competency of village midwives on caring intention toward maternal health. Interpersonal competency creates warm and close relationship, which makes midwives be having more sensitive feeling patient's need. Ninety eight village midwives in Kediri District, East Java Province, participate in this study. Two scales of Likert model are utilized. The Caring Intention toward Maternal Health Scale has 3 aspects i.e. self objectives to reach, active efforts to fulfill normative hope; and perceived of control behavior. The Competency Scale has 5 aspects i.e. initiatives, self disclosure, assertiveness, giving emotional support, and conflict management. Result of this study indicates that there is a positive correlation between the interpersonal competency variable and the caring intention of maternal health variable (r = 0.628 with p<0.01). The effective contribution from interpersonal competency to caring intention to achieve is 39.5%, while the rest percentage is influenced by other factors such as individual differences, social norms, and also clinical skills.